ANALISA PEMELIHARAAN PREVENTIF BABY INKUBATOR - Harahap, Gunawan Fahri; Sijabat, Salomo; Situmorang, Harold; Dabukke, Hotromasari (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Baby incubator is a tool that has a function as a treatment and temperature adjustment (heater) for premature babies who really need a temperature that is in accordance with the temperature in the mother's womb. The Baby Incubator uses a heating element that is controlled by a temperature control circuit so that the temperature remains stable. the heater will work when the temperature is less than the predetermined temperature, on the contrary if the temperature sensor is greater than the temperature setting it will automatically turn off. Medical equipment, of course, cannot be separated from damage, both light and heavy, because damage can be caused by improper use of standard operating procedures (SOP), lack of maintenance/maintenance, and incidents/accidents caused by human error. Based on the observations that have been made by the author, it is known that medical equipment requires periodic maintenance to ensure the quality of health services. Preventive maintenance of the baby incubator. Preventive maintenance is maintenance and care activities carried out to prevent damage. Preventive maintenance can be carried out daily or monthly.